Wildfowl survey in south-west Asia: progress in 1966 - Savage, Christopher (Wildfowl, 1967)
In the spring of 1966 the Survey received a grant from the World Wildlife Fund which greatly stimulated its development. International liaison was promoted through visits to Tehran, Baghdad, Cairo, Kabul and Bombay, where preparations were laid for participation in the January 1967 International Wildfowl Census. The I.W.R.B. Warsaw Conference on co-ordination of wildfowl research was attended by the writer; the decision to set up an Asiatic Wildfowl Working Group was one of the results of the conference. Ringing efforts were intensified during the year with a start being made in three new areas, Iran, Iraq and Assam. There was, however, no significant improvement in the return of Russian rings from south-west Asia. Of special interest during the year was the discovery that the White-headed Duck Oxyura leucocephala moults its flight feathers in West Pakistan in November, and the discovery that the Snow Goose Anser caerulescens and Bean Goose Anser fabalis had been wrongly included in the fauna of India and Pakistan. There was also encouraging news of the White-winged Wood Duck Cairina scutulata from Assam.